Hybrid warfare case studies - Croatia and Ukraine - Akrap, Gordan (Array, 2020)
Croatia’s Homeland war and aggression to Ukraine are clear examples that can be described with term Hybrid warfare. Different phases during conflict and war (every conflict is not a war; every war is a conflict) has a lot of similarities, but also has a difference. It is important to make deeper analysis to provide better and efficient lessons-learned preventive and active measures for future conflicts. This article starts with a short overview of Croatia’s Homeland war and continues with short overview of Ukrainian experience. It contains lessons-learned tools and suggestions for future activities.